2010
DOI: 10.17221/36/2009-jfs
|View full text |Cite
|
Sign up to set email alerts
|

The extent of root rot damage in Norway spruce stands established on fertile sites of former agricultural land

Abstract: The aim of this study was to compare the degree of root rot damage in two large complexes of Norway spruce stands established on former agricultural land at fertile sites. The root rot infection was observed on the stump cutting area on both intended and salvage clear fellings. Stands in Kružberk area in the Nízký Jeseník Mts. established on arable land showed very poor stability and large root rot damage at the age of 40–50 years. In contrast, stands in Lužná area in the Javorníky Mts., founded on former shee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…According to forest survey report, B1 stand has been growing on brown soil, while B2 stand -on less fertile rusty soil. There are explicit evidences that spruce trees which grow on fertile forest sites are more affected by root and boot rot than those on poorer sites (Lech, Żółciak 2006;Mareš 2010).…”
Section: Tab 2 Number Of Trees In Damage Classes and Respective Permentioning
confidence: 99%
“…According to forest survey report, B1 stand has been growing on brown soil, while B2 stand -on less fertile rusty soil. There are explicit evidences that spruce trees which grow on fertile forest sites are more affected by root and boot rot than those on poorer sites (Lech, Żółciak 2006;Mareš 2010).…”
Section: Tab 2 Number Of Trees In Damage Classes and Respective Permentioning
confidence: 99%
“…Modelling based on stump infection rate with Heterobasidion in spruce stands revealed that former pastures and arable lands are more susceptible to root rot than forest stands [28]. A more recent study form Czech Republic indicated differences in infection rate among different previous land uses, indicating higher infection in former arable lands than in former pastures [29].…”
Section: Introductionmentioning
confidence: 97%